Intellectual Deviation and its Impact on the Contemporary Generation in Islamic Thought (Causes – Treatments) - Hamed Hadi Baden Salamlan / Khalil Hassan Rahak Al-Zarkani ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The intellectual deviation of those who consider themselves Muslims, kill Muslims in the name of religion and carry the banner of God is greatest and slaughter Muslims with it. What made them in this is their lack of understanding of the religion and their adherence to their false opinions that have no root in Islam. When you disagree with him, it is permissible for him to kill you. The deviant has no dialogue, either you are with him or he kills you, and among them is a large group that has damaged the reputation of Islam called (ISIS).They are the takfiris whom the zealous Sons of Iraq fought with in all their combative forms, including the army, the police, and the Popular Mobilization force(AlHashid), in the battle to restore landand honor. That battle was based on a blessed fatwa from the supreme religious authority, His Eminence, the Grand Ayatollah, Sayyid Ali al-Husseini al-Sistani. Our Islamic religion commands us to love for our brothers as we love for ourselves, and to hate them as we hate ourselves. Moderation in behavior, purity in the soul, apologizing for error, and holding oneself accountable for sin, so whoever follows the path of Islam and follows the path of the religion of prophet Muhammad. He will only see good and tranquility in this world and the hereafter. Society today is in dire need of the spirit of tolerance and peaceful coexistence among the people of the same religion. Because today, with God’s help, we are strong with our unity, and that discrimination and wrong religious education stem from the human soul that was filled with hatred and arrogance and spread corruption in the country. We must eradicate the pain of division with our unity that defeated the greedy enemies. The absence of the family role produces a behavioral disorder in society, which leads to bad manners in people, which generates an aversion to the person in society. People become disinterested in terms of the family, and consequently, families become disengaged from community care in education, Like polytheists and infidels arguing about falsehood without knowledge